Prospective validation of the Emergency Surgery Score in emergency general surgery: An Eastern Association for the Surgery of Trauma multicenter study. Issue 1 (July 2020) - Kaafarani, Haytham M.A.; Kongkaewpaisan, Napaporn; Aicher, Brittany O.; Diaz, Jose J.; O'Meara, Lindsay B.; Decker, Cassandra; Rodriquez, Jennifer; Schroeppel, Thomas; Rattan, Rishi; Vasileiou, Georgia; Yeh, D. Dante; Simonoski, Ursula J.; et al.
Abstract : BACKGROUND: The Emergency Surgery Score (ESS) was recently developed and retrospectively validated as an accurate mortality risk calculator for emergency general surgery. We sought to prospectively validate ESS, specifically in the high-risk nontrauma emergency laparotomy (EL) patient. METHODS: This is an Eastern Association for the Surgery of Trauma multicenter prospective observational study. Between April 2018 and June 2019, 19 centers enrolled all adults (aged >18 years) undergoing EL. Preoperative, intraoperative, and postoperative variables were prospectively and systematically collected. Emergency Surgery Score was calculated for each patient and validated using c-statistic methodology by correlating it with three postoperative outcomes: (1) 30-day mortality, (2) 30-day complications (e.g., respiratory/renal failure, infection), and (3) postoperative intensive care unit (ICU) admission. RESULTS: A total of 1, 649 patients were included. The mean age was 60.5 years, 50.3% were female, and 71.4% were white. The mean ESS was 6, and the most common indication for EL was hollow viscus perforation. The 30-day mortality and complication rates were 14.8% and 53.3%; 57.0% of patients required ICU admission. Emergency Surgery Score gradually and accurately predicted 30-day mortality; 3.5%, 50.0%, and 85.7% of patients with ESS of 3, 12, and 17 died after surgery, respectively, with a c-statistic of 0.84. Similarly, ESS gradually and accurately predicted complications; 21.0%, 57.1%, and 88.9% of patients with ESS of 1, 6, and 13 developed postoperative complications, with a c-statistic of 0.74. Emergency Surgery Score also accurately predicted which patients required intensive care unit admission (c-statistic, 0.80). CONCLUSION: This is the first prospective multicenter study to validate ESS as an accurate predictor of outcome in the EL patient. Emergency Surgery Score can prove useful for (1) perioperative patient and family counseling, (2) triaging patients to the intensive care unit, and (3) benchmarking the quality of emergency general surgery care. LEVEL OF EVIDENCE: Prognostic study, level III.